FASL WASL AYAT GENDER DALAM PERSPEKTIF HERMENEUTIKA JURGEN HABERMAS - Hidayat, Nada Qaulan Sadida; Sopian, Asep; Nurmala, Mia (University of Islam Malang, 2024)
Gender inequality remains a prevalent issue in society today, despite the Quran's clear articulation of equality between men and women. This study aims to analyze verses of gender equality in the Quran that employ the linguistic devices of fasl and wasl using Jürgen Habermas's critical hermeneutical approach. Gender verses refer to those that specifically address gender roles, rights, and obligations in a religious context. The study adopts a linguistic approach to explore how fasl and wasl are used to convey gender-related messages in the Quran. It employs a qualitative content analysis methodology involving literature identification, selection, and analysis in Arabic. Purposive sampling is used to select verses from Surah An-Nisa’ , one of the longest chapters addressing gender, particularly women. From 176 verses, several excerpts depicting gender relations are analyzed. The findings reveal equality in inheritance, kinship, receiving divine blessings, leadership, and equal rewards. These aspects represent social, economic, and humanitarian rights.